"Migrating" or Being "Left Behind": The Education Dilemma of Rural Children in Mainland China. Issue 3 (4th May 2017) - Youlu, Shen
Abstract: Rural children belong to an educationally disadvantaged group whether they migrate or remain in their villages. Using a specially designed questionnaire, this paper surveyed more than 2, 500 migrant and left-behind children in the Xixiangtang District of Nanning in Mainland China on issues relating to education and mental state. Through comparisons of migrant and nonmigrant children and those who had and had not been left behind, this study found that migrant children are unable to enter public schools due to incomplete documents, and also experience problems with a safe commute to and from school, after-school care, etc.; left-behind children are more likely to experience problems with emotional deprivation, dull after-school life, susceptibility to disease, and poor habits. With respect to mental state, some of the survey questions showed no significant differences, whereas others displayed significant divergences. It can be seen that both migrant and left-behind children experience problems with educational difficulties, poor discipline, and poor mental adaptability, and are in a clearly disadvantaged position. This paper recommends that the government, schools, society, and families jointly cooperate to strengthen emotional guidance for migrant children and left-behind children and ensure that no child is abandoned, allowing migrant children to grow and learn healthily in their respective environments.